Scaling Down the European Model of Agriculture: The Case of the Rural Environmental Protection Scheme in Ireland - Lenihan, Martin H. (2012)
Recent reforms of the Common Agricultural Policy have led to much discussion of the European multifunctional model of agriculture in both policy and academic circles. Accordingly, European agriculture provides numerous social and environmental benefits and as a result should be supported through a system of payments which directly target those benefits. The agri-environmental measures specified under pillar II of the Common Agricultural Policy are supposed to exemplify the multifunctional model of agriculture, and the macro-level debates surrounding the introduction and evolution of these measures have been the subject of much scholarly research. However, very little research has been conducted into how the actors responsible for implementing these measures at the local level react to the macro-level definitions and interpretations of agri-environmental problems and their solution. This article examines the specific case of the Rural Environmental Protection Scheme in Ireland, focusing on how this scheme is viewed by diverse actors (farmers, government officials, and environmentalists) in the environmentally sensitive area known as the Burren, how these views complement or contradict the narrative of multifunctional agriculture promoted at the EU level of governance, and how this narrative is mediated by a national agri-environmental policy community. Results suggest the need to consider how policy narratives and instruments prominent at the macro-global level of governance enter into the life-worlds, cultures, and ecologies of a variety of actors at the national and local levels of governance, and in the process are reinterpreted, resisted, and transformed.